Os macrófagos treinados pelo bacilo Calmette-Guérin (BCG) exibem uma resposta inflamatória protetora contra a bactéria intracelular Brucella abortus - Ana Carolina Valente Santos Cruz de Araujo (2023)
The bacillus Calmette-Guérin (BCG) is the only licensed vaccine for use in tuberculosis control. It has also the ability to trigger non-specific immune protection against viral and bacterial infections. These beneficial side effects have been related to the innate immune system, a phenomenon known as trained immunity. When comprising the bone marrow (BM) compartment, this phenomenon represents a lasting immune memory. Our hypothesis is that BCG-trained immunity is protective against infection by the bacterium B. abortus, responsible for causing brucellosis, an infectious and systemic zoonosis that has an impact on human and animal health. In this study, we demonstrate that C57BL/6 mouse bone marrow-derived macrophages (BMDMs) under BCG training enhance inflammatory responses against B. abortus. BCG-trained macrophages showed increased MHC-II and CD40 expression on cell surface and higher IL-6, IL-12 and IL-1β production. The increase in IL-1β secretion was accompanied by enhanced activation of canonical and non-canonical inflammasome platforms. We observed elevated caspase-11 expression and caspase-1 processing in BCG-trained macrophages in response to B. abortus compared to untrained cells. In addition, these BCG-trained cells showed higher NLRP3 expression after B. abortus infection. From a metabolic point of view, signaling through the Akt/mTOR/S6K pathway was also increased. Additionally, BCG-training resulted in higher iNOS expression and nitrite production, culminating in an improved macrophage killing capacity against intracellular B. abortus. In vivo, we monitored a significant reduction in the bacterial burden in organs from BCG-trained C57BL/6 mice when compared to the untrained group. Furthermore, previous BCG-immunization of RAG-/- mice partially protects against Brucella infection, suggesting an important role of the innate immune compartment in this scenario. Lastly, naive recipient mice that received BM transfer (BMT) from BCG-trained donors showed greater resistance to B. abortus when compared to the untrained counterparts. These results demonstrate BCG-induced trained immunity in mice results in better control of intracellular B. abortus in vivo and in vitro.